O consumo das famílias no Brasil entre 2000 e 2013: Uma análise estrutural a partir de dados do sistema de contas nacionais e da pesquisa de orçamentos familiares - Sandro Sacchet de Carvalho; Cláudio Hamilton dos Santos; Vinícius Augusto de Almeida; Yannick Kolai Zagbai Joel; Karine Cristina Paiva; Luíza Freitas Caldas (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– Household consumption is the most important component of gross domestic product (GDP) and its dynamics is crucial to understanding the changes in the dynamics of the economy in boom periods and crises. This paper analyzes the structure of household consumption in Brazil between the years 2000 and 2013 from its two main sources of data, the System of National Accounts (SNA) and the Family Budget Survey (POF), both produced the Brazilian Institute of Geography and Statistics (IBGE); as well as carry out a comparative analysis of the differences between the two sources. The results show that both surveys revealed changes in household consumption structure during this economic period of growth and income distribution, such as a larger share of consumption in durable goods (cars, appliances etc.). However, the differences between the two sources are substantial.
Keywords: D12; E01; E21; 330; household consumption; national accounts; household surveys